Improved link analysis method for user interface design - modified link table and optimisation-based algorithm - Lin, Cheng-Jhe; Wu, Changxu (Behaviour & information technology, 2010)
Link analysis (LA) is one of most widely used methods in user interface design to arrange control elements on user interfaces. However, traditional LA method is insufficient for evaluating transitional cost associated with accessibility (the easiness for the operator to reach certain control element on the interface) and the link table commonly used contains no directional information for assessing difficulty. To address these two problems, an improved LA method based on a modified link table and a branch-and-bound algorithm is proposed in this study. A case study on a simplified control interface of a boiling water reactor (BWR) in a real-world nuclear control system was exemplified to elucidate the improved method and an experiment was conducted to validate the effectiveness of the method in improving users' performance time. The results showed that the total completion time (CT) and the completion time of accessibility-associated operations were significantly shorter on the interface modified by the improved method than by the traditional LA method, while the difference of the completion time of proximity-associated operations between the two interfaces was non-significant. Therefore, although the traditional LA method can significantly ameliorate the random interface by optimising the proximity between control elements, the improved method can further improve the CT by optimally trading off the accessibility and proximity. The method can be applied to the interface which requires physical movements between the user and the interface and within the interface, especially touch screen and control panels.